2017
DOI: 10.1161/circinterventions.116.004428
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes After Decompression of the Right Ventricle in Infants With Pulmonary Atresia With Intact Ventricular Septum Are Associated With Degree of Tricuspid Regurgitation

Abstract: Patients with pulmonary atresia with intact ventricular septum deemed suitable for RV decompression have a high reintervention burden although most achieve 2-ventricle circulation. TR ≤mild at baseline is strongly associated with reintervention and <2-ventricle circulation at medium-term follow-up. Degree of baseline TR may be an important marker of long-term outcomes in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 25 publications
0
68
1
Order By: Relevance
“…Over the study period, 103 neonates underwent RV decompression for PA‐IVS. Patient characteristics, procedural details and outcomes were previously reported . In brief, there were two procedural deaths.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the study period, 103 neonates underwent RV decompression for PA‐IVS. Patient characteristics, procedural details and outcomes were previously reported . In brief, there were two procedural deaths.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a case control study to assess echocardiographic parameters associated with achievement of a 2V circulation and with RV growth. This was a post hoc analysis of a previously performed study of clinical outcomes in patients with PA/IVS who underwent RV decompression in the neonatal period . The patient population consisted of all infants with PA/IVS who underwent RV decompression at less than 30 days of age between January 1, 2005 and May 1, 2015 at four large pediatric centers (Children’s Healthcare of Atlanta, Children’s Hospital of Philadelphia, Cincinnati Children’s Hospital Medical Center, and Texas Children’s Hospital).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports on PA-IVS had largely been limited to single-center, small cohort studies, and many of the larger series were hindered by a broad span of inclusion dates (some spanning multiple decades of institutional experience), or very small cohorts where more contemporary approaches were employed but statistical power was wanting ( Figure 1). 17 Additional analyses led to an enhanced understanding of the importance of nuanced technical variables on outcomes. We evaluated a host of echocardiographic and hemodynamic factors and identified that preintervention tricuspid regurgitation was associated with a host of important clinical end points following right ventricle decompression in neonates with PA-IVS.…”
Section: His Torymentioning
confidence: 99%